2013
DOI: 10.1175/jas-d-12-0293.1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical and Physical Processes Leading to Tropical Cyclone Intensification under Upper-Level Trough Forcing

Abstract: The rapid intensification of Tropical Cyclone (TC) Dora (2007, southwest Indian Ocean) under upper-level trough forcing is investigated. TC–trough interaction is simulated using a limited-area operational numerical weather prediction model. The interaction between the storm and the trough involves a coupled evolution of vertical wind shear and binary vortex interaction in the horizontal and vertical dimensions. The three-dimensional potential vorticity structure associated with the trough undergoes strong defo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 52 publications
1
22
1
Order By: Relevance
“…Previous studies also indicated that the increased convergence of eddy angular momentum resulting from the interaction of TCs with upper-level disturbances may facilitate TC intensification (e.g., Molinari and Vollaro 1989;Davidson and Kumar 1990;DeMaria et al 1993;Hanley et al 2001;Hanley 2002). Cyclonic potential vorticity (PV) advection toward the TC core during such events has also been demonstrated to play a role in TC intensification (e.g., Molinari et al 1995Molinari et al , 1998Montgomery and Farrell 1993;Leroux et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also indicated that the increased convergence of eddy angular momentum resulting from the interaction of TCs with upper-level disturbances may facilitate TC intensification (e.g., Molinari and Vollaro 1989;Davidson and Kumar 1990;DeMaria et al 1993;Hanley et al 2001;Hanley 2002). Cyclonic potential vorticity (PV) advection toward the TC core during such events has also been demonstrated to play a role in TC intensification (e.g., Molinari et al 1995Molinari et al , 1998Montgomery and Farrell 1993;Leroux et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that 78% of superposition and 61% of distant interaction cases deepened. Although these results confirm that interaction favors TC intensification in a statistical sense, to identify whether or not a particular trough interaction is conducive to TC intensification is still not straightforward (Hanley et al, 2001;Leroux et al, 2013). Besides, these two studies ignored the role of upper-level inertial stability, emphasized in a number of other studies (e.g., Holland and Merrill, 1984;Rappin et al, 2011).…”
Section: Tc Interactionmentioning
confidence: 78%
“…17), so that their warm core structure will not be destroyed by persistently strong VWS. Besides, interaction should not last more than around two days, playing its role as a triggering effect for initiating wind-induced surface heat exchange (Emanuel, 1986) or the eyewall replacement cycle (Willoughby et al, 1982;Leroux et al, 2013), as long-lasting interaction will eventually bring persistent VWS, which is destructive to a TC's warm core. Finally, interaction should appear at low latitudes so that environmental inertial stability is relatively weak and thus the TC's axisymmetric secondary circulation is more sensitive to the upper-level asymmetric forcing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the focus of the research community is mostly toward the dynamics of the storm's inner core within ;200 km of the storm center, the review presented at the Eighth WMO International Workshop on Tropical Cyclones (IWTC-8; Leroux et al 2014) indicates that continued study of external influences on TC intensity change is warranted because the environment hostility controls both the development and predictability of TCs (Zhang and Tao 2013;Tao and Zhang 2014). The knowledge gaps or suitable research routes regarding the problem of TC intensity change under external influences are summarized in a comprehensive sketch (Leroux et al 2014, see their Fig.…”
Section: Introductionmentioning
confidence: 99%